2022
DOI: 10.3390/life12071003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis Reveals Differential Gene Expression in Resistant and Susceptible Watermelon Varieties in Response to Meloidogyne incognita

Abstract: M. incognita is a major parasitic plant disease in watermelon production, causing serious economic losses. Although there are many studies on root-knot nematode, the resistance mechanism is still unclear. In this study, in order to fully understand the mechanism of watermelon resistance to root-knot nematode, the relatively strongly resistant ‘Hongzi watermelon’ variety and the susceptible ‘M16’ watermelon variety were used as materials, combined with RNA sequencing (RNA-seq), to analyze the expression abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…46 It has been reported that overexpression of CCR and 4CL genes in watermelon enhances resistance to Meloidogyne incognita. 44 The results indicated that B. velezensis WB could induce the systemic resistance of watermelon by stimulating phenylpropanoid metabolism in the presence of Fon. In addition, PAL, 4CL, CCR and POD enzymes are involved in lignin biosynthesis in plants.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…46 It has been reported that overexpression of CCR and 4CL genes in watermelon enhances resistance to Meloidogyne incognita. 44 The results indicated that B. velezensis WB could induce the systemic resistance of watermelon by stimulating phenylpropanoid metabolism in the presence of Fon. In addition, PAL, 4CL, CCR and POD enzymes are involved in lignin biosynthesis in plants.…”
Section: Discussionmentioning
confidence: 94%
“…demonstrated that the expression of PAL was induced successfully in parsley ( Petroselinum crispum L.) pre‐treatment with benzothiadiazole (BTH) 46 . It has been reported that overexpression of CCR and 4CL genes in watermelon enhances resistance to Meloidogyne incognita 44 . The results indicated that B. velezensis WB could induce the systemic resistance of watermelon by stimulating phenylpropanoid metabolism in the presence of Fon.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations